MEK/ERK signaling pathway is required for enterovirus 71 replication in immature dendritic cells - Shi, Weifeng (Virol J, 2014)
BACKGROUND: The mitogen-activated protein kinase kinase/extracellular-signal-regulated kinase (MEK/ERK) signaling pathway is involved in viral life cycle. However, the effect of MEK/ERK pathway in enterovirus 71(EV71)-infected immature dendritic cells (iDCs) is still unclear. METHODS: Human peripheral blood mononuclear cells (PBMCs) were isolated and induced to generate iDCs. Unifected iDCs and EV71-infected iDCs with a multiplicity of infection (MOI = 5) were analyzed by flow cytometry. Differential gene expressions of MEK/ERK signaling pathway molecules in EV71-infected iDCs were performed by PCR arrays. The phosphorylation of MEK/ERK pathway molecules in EV71-infected iDCs preincubated without or with U0126 (20 μM) at indicated times was detected by Western blot. The concentrations of IL-1α, IL-2, IL-6, IL-12, TNF-α, IFN-α1, IFN-β and IFN-γ in culture supernatant were analyzed by the luminex fluorescent technique. RESULTS: When iDCs were infected with EV71 for 24 h, the percentage of CD80, CD83, CD86 and HLA-DR expressed on iDCs significantly increased. PCR arrays showed that gene expressions of molecules in MEK/ERK signaling pathway were remarkably upregulated in EV71-infected iDCs. EV71 infection activated both MEK1/2 and ERK1/2, which phosphorylated their downstream transcription factor c-Fos, c-Jun, c-myc and Elk1. Importantly, the treatment of U0126 significantly inhibited MEK/ERK signaling pathway molecules and severely impaired virus replication., Additionally, EV71 infection promoted the expression of son of sevenless (SOS1) and increased the secretion of IL-1α, IL-2, IL-6, IL-12, TNF-α,IFN-β and IFN-γ. Furthermore,the release of IL-1α, IL-2,IL-6 and TNF-α could be effectively suppressed by inhibitor U0126. CONCLUSIONS: Our data suggest that the MEK/ERK signaling pathway plays an important role in EV71-infected iDCs and these molecules may be potential targets for the development of new anti-EV71 drugs.